Bisindo Sign Language Transliteration Using Automata - Pratomo, Awang Hendrianto; Simanjuntak, Oliver S.; Putra, Dimas Candra Nugraha (Compiler, 2019)
Sign Language is a language which prioritizes manual communication, body language and lip movement for communication. People who usesign language for communication aredeaf and mute people. Sign language in Indonesia is Sistem Isyarat Bahasa Indonesia (SIBI) and Bahasa Isyarat Indonesia (BISINDO). BISINDO has a unique clause pattern that isSOPA (Subject, Object, Predicate, Adverbial). The clause pattern of BISINDO is just for deaf and mute people who know and understand it. Because there are some different structures between Indonesian language and BISINDO, itis neededlearning media which can translate from Indonesian language to BISINDO. Finie State Automata (FSA) is a method which is able to recognize pattern sentence classification in Indonesian language. FSA method is NSA (Non-DetermisticFinie State Automata) that is otomata with characteristics as a state. NFA is used to give introducing structure pattern sentence in Indonesian language. Sentence pattern which is produced from NFA produces eight sentences pattern which are arranged as requisites ofBISINDO translation. The result of research which is experimented by sign language researchersas many as 90% can translate well and appropriate with BISINDO sentence pattern, 10% explain that it is not appropriate with translation of sentence pattern and sign language model. Based on the data, it can be known that media of BISINDO sign language learning based on web using method of translation automata can be used for learning media.